2021
DOI: 10.3168/jds.2020-18270
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide inhibits triglyceride synthesis in dairy cow mammary epithelial cells by upregulating miR-27a-3p, which targets the PPARG gene

Abstract: The fat content of milk determines the quality of milk, and triglycerides are the major components of milk fat. Milk fat synthesis is regulated by many factors. Lipopolysaccharide (LPS) has been shown to inhibit milk fat synthesis in bovine mammary epithelial cells, but research on the underlying mechanisms has been limited. MicroRNA (miRNA) are involved in many physiological processes, but there have been few studies on their regulation in milk fat synthesis. In this study, we aimed to investigate whether LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Bovine mammary epithelial cells (BMECs) were isolated from bovine mammary gland tissue and cultured in vitro, and they showed limited passaging ability. MAC-T cells are a bovine mammary epithelial cell line widely used in mastitis-related research [ 87 , 88 ]. Mojisola Ogunnaike et al showed that the miRNA and protein profiles in MAC-T-cell-derived exosomes were consistent with those of exosomes derived from milk, and hence, MAC-T cells can be powerful tools for milk exosome-related research [ 89 ].…”
Section: Exosomes Associated With Mastitismentioning
confidence: 99%
“…Bovine mammary epithelial cells (BMECs) were isolated from bovine mammary gland tissue and cultured in vitro, and they showed limited passaging ability. MAC-T cells are a bovine mammary epithelial cell line widely used in mastitis-related research [ 87 , 88 ]. Mojisola Ogunnaike et al showed that the miRNA and protein profiles in MAC-T-cell-derived exosomes were consistent with those of exosomes derived from milk, and hence, MAC-T cells can be powerful tools for milk exosome-related research [ 89 ].…”
Section: Exosomes Associated With Mastitismentioning
confidence: 99%
“…In recent years, various studies have shown that bovine mammary epithelial cells respond to the invasion of bacteria or their waste metabolic products by changing the expression levels of certain genes involved in inflammatory processes and immunity in vitro [178][179][180]. For example, it was recently found that the expression of miR-27a-3p in mammary epithelial cell cultures from dairy cows is significantly increased by the administration of lipopolysaccharide, which is a key antigenic factor for bacterial mastitis pathogens [181]. Mastitis is the most common inflammatory udder disease of dairy cattle, usually caused by bacterial infection [182].…”
Section: Immunological Role Of Mammary Gland Mirnas and Their Functions In Breast Diseasesmentioning
confidence: 99%
“…The milk-fat levels and composition are affected by various factors, including heredity, nutrition, physiological conditions and the environment. More studies have revealed some miR-NAs affecting lipid metabolism by targeting genes, e.g., ATP binding cassette transporter A1 (ABCA1), with Chen et al reporting that miR-106b functions through ABCA1 by mRNA and protein levels [2]; however, the underlying mechanisms remain poorly understood [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miR-15a inhibits the vitality and lactation of mammary epithelial cells by targeting the GHR gene [26], which is associated with milk composition. Moreover, miR-27a-3p can inhibit milk-fat synthesis by dairy cow mammary epithelial cells (MAC-Ts) by targeting peroxisome proliferator-activated receptor gamma (PPARG), which enhances the synthesis of monounsaturated fatty acids by controlling stearoyl-CoA desaturase [4].…”
Section: Introductionmentioning
confidence: 99%